2020
DOI: 10.1111/nph.16519
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin‐induced protein synthesis suppresses growth and osmotic stress tolerance

Abstract: Cytokinins control critical aspects of plant development and environmental responses. Perception of cytokinin ultimately leads to the activation of proteins belonging to the type-B Response Regulator family of cytokinin response activators. In Arabidopsis thaliana, ARR1 is one of the most abundantly expressed type-B Response Regulators.We investigated the link between cytokinin signaling, protein synthesis, plant growth and osmotic stress tolerance.We show that the increased cytokinin signaling in ARR1 gain-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…Next, in a parallel experiment, the three-day-old seedlings were deprived of water for 24 h, reaching the relative water content 83.2 ± 0.4% of control roots, and the identified cytokinin-responsive proteins were quantified (Tables 1, 2, Supplementary Table S1). The results confirmed that cytokinin-responsive proteins significantly overlapped with the drought-responsive subset which is well in line with the previous reports suggesting that cytokinin may induce osmotic stress hypersensitivity (Karunadasa et al, 2020). In total, out of 70 identified drought-responsive proteins, 39 were cytokininresponsive and the response to cytokinin and drought was similar for 35 of these, including an accumulation of the subunit of a voltage-gated potassium channel (HORVU6Hr1G091250), annexin (HORVU6Hr1G074440) and depletion of ferredoxinnitrite reductase (HORVU6Hr1G080750) and multiple enzymes of carbohydrate and amino acid metabolism.…”
Section: Cytokinin Treatment Elicited Drought-stress Response In Barlsupporting
confidence: 92%
“…Next, in a parallel experiment, the three-day-old seedlings were deprived of water for 24 h, reaching the relative water content 83.2 ± 0.4% of control roots, and the identified cytokinin-responsive proteins were quantified (Tables 1, 2, Supplementary Table S1). The results confirmed that cytokinin-responsive proteins significantly overlapped with the drought-responsive subset which is well in line with the previous reports suggesting that cytokinin may induce osmotic stress hypersensitivity (Karunadasa et al, 2020). In total, out of 70 identified drought-responsive proteins, 39 were cytokininresponsive and the response to cytokinin and drought was similar for 35 of these, including an accumulation of the subunit of a voltage-gated potassium channel (HORVU6Hr1G091250), annexin (HORVU6Hr1G074440) and depletion of ferredoxinnitrite reductase (HORVU6Hr1G080750) and multiple enzymes of carbohydrate and amino acid metabolism.…”
Section: Cytokinin Treatment Elicited Drought-stress Response In Barlsupporting
confidence: 92%
“…The ribosome composition reflects external stimuli, and may have a significant impact on plant responses [41]. Previous proteomics reports have indicated that ribosome could be the target of cytokinin signaling [33,42,43]. Here, 122 and 167 ribosomal proteins were identified in seedling and shoot proteome, respectively.…”
Section: Cytokinin Response Targets Ribosomal Proteinsmentioning
confidence: 86%
“…Here, 122 and 167 ribosomal proteins were identified in seedling and shoot proteome, respectively. First, 60S ribosomal proteins L4-1 and L4-2, previously implicated in response to cytokinin [43], were quantified in both experiments, but there was not any detectable difference compared to the mock-treated plants (Figure 9, L4e). The abundances of only three ribosomal proteins were significantly altered in early INCYDE response.…”
Section: Cytokinin Response Targets Ribosomal Proteinsmentioning
confidence: 90%
“…Ribosomal proteins (RPs) are essential components of ribosomes, which are ubiquitous ribonucleoprotein bodies responsible for protein synthesis (Opron and Burton, 2019;Ghulam et al, 2020). Plant cells regulate protein synthesis in response to nutrients and stress by controlling RP expression (Szakonyi and Byrne, 2011;Karunadasa et al, 2020). In this study, the most prominent cluster was related to ribosome function (Figure 8) and enriched in the PPI network, suggesting an important role of ribosome biogenesis/translation in the Pi-starvation response.…”
Section: Pi-responsive Dfasps Regulated During Pi Starvationmentioning
confidence: 62%